Aquatic Therapy Following Total Knee Replacement - E. Endang Sri Mariani (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
ABSTRACTTotal knee replacement (TKR) has revolutionized the care of pati ents with end-stage knee joint disease. Rehabilitation of TKR commonly consists of land-based exercises as a primary mode, but it may notalways be an optimal approach. Water provides a unique environment. The level of exertion is a function of water properties and the physical laws of motion. Aquatic therapy allows fine gradations of exercise, increase control over thepercentage of weight bearing, increase ROM and strength, decrease pain and swelling, and increase confidence in functional movements.Although there is inconsistency in research results, of all studies aquatic therapy is not said to be worst than land-based therapy. Moreover, it has a positive influence on social behavior and mood. This may bemore advantageous in the early postoperative phase when patient s are limited by pain. As a tool, aquatic therapy has desirable and undesirable effects. So, it is important to screen the patientsbefore undergoing aquatic therapy and to assess patient’s condition during and after it. However, so far there has been no agreement in post TKR aquatic protocols. The obstacle also may occur on the cost forfacility maintenance and hygiene, as well as the availability o f competent human resources.Keywords: aquatic therapy, total knee replacement